2003
DOI: 10.1038/sj.bjc.6600806
|View full text |Cite
|
Sign up to set email alerts
|

L523S, an RNA-binding protein as a potential therapeutic target for lung cancer

Abstract: Approaches to vaccine-based immunotherapy of human cancer may ultimately require targets that are both tumour-specific and immunogenic. In order to generate specific antitumour immune responses to lung cancer, we have sought lung cancer-specific proteins that can be targeted for adjuvant vaccine therapy. By using a combination of cDNA subtraction and microarray analysis, we previously reported the identification of an RNA-binding protein within the KOC family, L523S, to be overexpressed in squamous cell cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
93
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(98 citation statements)
references
References 17 publications
4
93
1
Order By: Relevance
“…Previous data has shown that IMP3 expression is not tumor specific. 3,4,9 It is more likely that IMP3 is a marker of malignancy. IMP3 overexpression has been reported in carcinomas of the stomach, colon, A large body of epidemiologic and molecular data has shown that high-risk types of the human papillomavirus (HPV) are the etiologic agents for most cases of endocervical glandular neoplasia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous data has shown that IMP3 expression is not tumor specific. 3,4,9 It is more likely that IMP3 is a marker of malignancy. IMP3 overexpression has been reported in carcinomas of the stomach, colon, A large body of epidemiologic and molecular data has shown that high-risk types of the human papillomavirus (HPV) are the etiologic agents for most cases of endocervical glandular neoplasia.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-like growth factor-II mRNA-binding protein 3 (IMP3) known in previous publications as L523S or KOC (K-homologous domain containing protein overexpressed in cancer), 3,4 is a newly identified oncofetal RNA-binding protein that binds to mRNAs such as insulin-like growth factor-II (IGF-II) transcripts. IMP3 is expressed during embryogenesis but not in most adult tissues.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…13,16,17 Increased levels of IMP-3 have been identified in pancreatic carcinoma, renal cell carcinoma, germ cell neoplasms, ovarian carcinoma, and extrapulmonary small-cell carcinoma, as well as high-grade neuroendocrine carcinoma, squamous cell carcinoma, and adenocarcinoma of the lung. [16][17][18][19][20][21] Additionally, IMP-3 was shown to be a prognostic marker in patients with renal cell carcinoma, with lack of expression in the primary tumor predicting longer metastases-free survival. 22 IMP-3 expression increases with grade of dysplasia in pancreatic ductal epithelium and with tumor stage in pancreatic carcinoma.…”
mentioning
confidence: 99%
“…22 IMP-3 expression increases with grade of dysplasia in pancreatic ductal epithelium and with tumor stage in pancreatic carcinoma. 19 Finally, two studies demonstrating inhibition of cell proliferation after knockdown of IMP-3 in human K562 leukemia cells 15 and an immunogenic response to administration of IMP-3 in lung cancer patients 21 show promise for IMP-3 as a potential target molecule for cancer therapy.…”
mentioning
confidence: 99%